MANAJEMEN ASET DAN KEMAMPULABAAN PERUSAHAAN PADA PERIODE KRISIS DAN PASKA PERIODE KRISIS (Studi pada perusahaan manufaktur go public di Bursa Efek Indonesia) - Ruhadi Ruhadi (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2013)
This study aims to identify the impact of asset management to corporate profit ablitiy of the manufacturing companies in Indonesian Stock Exchanges. By using the data of 20 manufacturing public companies which listed on the Indonesian Stock Exchange. This study involves 140 units of observation in the post-crisis period and 40 units of  observation in the period of crisis. By using regression analysis and analysis of variance found that there are positive and significant  influence between asset management to the corporate profit abilities of both crisis or post-crisis period on the Indonesian Stock Exchange. However there was nostatistically significant difference between the asset management in the period of crisis with the post-crisis period. Thus, it can be concluded that assets productivity of manufacturing companies do the same, either incrisis or post-crisis period, but the impact of asset management companies to the corporate profit abilities in post-crisis period is much better compared with the period of crisis.